Selected problems of precise injection molding. Part I. Dimensions and dimensional stability of precise moldings - Bociąga, E.; Jaruga, T. (Polimery, 2022)
In the literature review the general characteristic of precise injection molding process was presented. The features distinguishing this process from the conventional injection molding are specified (Table 1). The process of precise injection molding makes possible to produce the moldings showing strictly defined quality features, mainly high precision and repeatability of dimensions and shapes as well as very good surfaces. Special attention has been paid to the relations among particular stages of the process discussed and changes of moldings' dimensions (Fig. 1) and to the factors determining the quality of the products obtained (Fig. 2).